Experimental Study of the Heat Transfer Enhancement from a Circular Cylinder in Laminar Pulsating Cross-flows. Issue 6 (12th April 2016) - Li, Guoneng; Zheng, Youqu; Hu, Guilin; Zhang, Zhiguo; Xu, Yousheng
Abstract : Experiments were designed to investigate the heat transfer enhancement from a single heated circular cylinder in laminar pulsating cross-flows. Several parameters were explored, including Strouhal number between 0.18 and 2.80, Reynolds number between 205 and 822, and pressure amplitude prms between 40 Pa and 276 Pa. It was observed that the heat transfer enhancement factor increased up to 2.10, and an empirical correlation between the convection heat transfer coefficient and pulsating flows was developed. Results found that the heat transfer enhancement factor decreases with Strouhal number. Increasing Reynolds number was found to have a negative impact on the heat transfer enhancement factor when the pulsating frequency is relatively low, but with a higher pulsating frequency, an increasing Reynolds number increases the heat transfer enhancement factor. Larger pressure amplitude was found to continuously produce larger heat transfer enhancement factor when both Strouhal number and Reynolds number are kept constant.